2021-10-12 12:30:28 +01:00
|
|
|
---
|
|
|
|
author: Alvie Rahman
|
|
|
|
date: \today
|
2021-11-17 14:54:49 +00:00
|
|
|
title: MMME1026 // Systems of Equations and Matrices
|
|
|
|
tags: [ uni, nottingham, mechanical, engineering, mmme1026, maths, systems_of_equations, matrices ]
|
2021-10-12 12:30:28 +01:00
|
|
|
---
|
2021-10-20 12:47:29 +01:00
|
|
|
# Systems of Equations (Simultaneous Equations)
|
2021-10-19 20:24:53 +01:00
|
|
|
|
|
|
|
## Gaussian Elimination
|
|
|
|
|
|
|
|
Gaussian eliminiation can be used when the number of unknown variables you have is equal to the
|
|
|
|
number of equations you are given.
|
|
|
|
|
|
|
|
I'm pretty sure it's the name for the method you use to solve simultaneous equations in school.
|
|
|
|
|
|
|
|
For example if you have 1 equation and 1 unknown:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
2x &= 6 \\
|
|
|
|
x &= 3
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
### Number of Solutions
|
|
|
|
|
|
|
|
Let's generalise the example above to
|
|
|
|
|
|
|
|
$$ax = b$$
|
|
|
|
|
|
|
|
There are 3 possible cases:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
a \ne 0 &\rightarrow x = \frac b a \\
|
|
|
|
a = 0, b \ne 0 &\rightarrow \text{no solution for $x$} \\
|
|
|
|
a = 0, b = 0 &\rightarrow \text{infinite solutions for $x$}
|
|
|
|
\end{align*}
|
|
|
|
|
2021-10-20 12:47:29 +01:00
|
|
|
### 2x2 Systems
|
2021-10-19 20:24:53 +01:00
|
|
|
|
|
|
|
A 2x2 system is one with 2 equations and 2 unknown variables.
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
3x_1 + 4x_2 &= 2 &\text{(1)} \\
|
|
|
|
x_1 + 2x_2 &= 0 &\text{(2)} \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
3\times\text{(2)} = 3x_1 + 6x_2 &= 0 &\text{(3)} \\
|
|
|
|
\text{(3)} - \text{(1)} = 0x_1 + 2x_2 &= -2 \\
|
|
|
|
x_2 &= -1
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
We've essentially created a 1x1 system for $x_2$ and now that's solved we can back substitute it
|
|
|
|
into equation (1) (or equation (2), it doesn't matter) to work out the value of $x_1$:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
3x_1 + 4x_2 &= 2 \\
|
|
|
|
3x_1 - 1 &= 2 \\
|
|
|
|
3x_1 &= 6 \\
|
|
|
|
x_1 &= 2
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
You can check the values for $x_1$ and $x_2$ are correct by substituting them into equation (2).
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
2021-10-20 12:47:29 +01:00
|
|
|
### 3x3 Systems
|
2021-10-19 20:24:53 +01:00
|
|
|
|
|
|
|
A 3x3 system is one with 3 equations and 3 unknown variables.
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
2x_1 + 3x_2 - x_3 &= 5 &\text{(1)} \\
|
|
|
|
4x_1 + 4x_2 - 3x_3 &= 5 &\text{(2)} \\
|
|
|
|
2x_1 - 3x_2 + x_3 &= 5 &\text{(3)} \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
The first step is to eliminate $x_1$ from (2) and (3) using (1):
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
\text{(2)}-2\times\text{(1)} = -2x_2 -x_3 &= -1 &\text{(4)} \\
|
|
|
|
\text{(3)}-\text{(1)} = -6x_2 + 3x_3 &= -6 &\text{(5)} \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
This has created a 2x2 system of $x_2$ and $x_3$ which can be solved as any other 2x2 system.
|
|
|
|
I'm too lazy to type up the working, but it is solved like any other 2x2 system.
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
x_2 &= -2
|
|
|
|
x_3 &= 5
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
These values can be back-substituted into any of the first 3 equations to find out $x_1$:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
-2x_1 + 3x_2 - x_3 = 2x_1 + 6 - 3 = 5 \rightarrow x_1 = 1
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
</details>
|
2021-10-20 12:47:29 +01:00
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 2
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
x_1 + x_2 - 2x_3 &= 1 &R_1 \\
|
|
|
|
2x_1 - x_2 - x_3 &= 1 &R_2 \\
|
|
|
|
x_1 + 4x_2 + 7x_3 &= 2 &R_3 \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
1. Eliminate $x_1$ from $R_2$, $R_3$:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
x_1 + x_2 - 2x_3 &= 1 &R_1' = R_1\\
|
|
|
|
- 3x_2 - 5x_3 &= -1 &R_2' = R_2 - 2R_1 \\
|
|
|
|
3x_2 + 5x_3 &= 1 &R_3' = R_3 - R_1 \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
We've created another 2x2 system of $R_2'$ and $R_3'$
|
|
|
|
|
|
|
|
2. Eliminate $x_2$ from $R_3''$
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
x_1 + x_2 - 2x_3 &= 1 &R_1'' = R_1' = R_1\\
|
|
|
|
- 3x_2 - 5x_3 &= -1 &R_2'' = R_2' = R_2 - 2R_1 \\
|
|
|
|
0x_3 &= 0 &R_3'' = R_3 '+ R_2' \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
We can see that $x_3$ can be any number, so there are infinite solutions. Let:
|
|
|
|
|
|
|
|
$$x_3 = t$$
|
|
|
|
|
|
|
|
where $t$ can be any number
|
|
|
|
|
|
|
|
3. Substitute $x_3$ into $R_2''$:
|
|
|
|
|
|
|
|
$$R_2'' = -3x_2 - 5t = -1 \rightarrow x_2 = \frac 1 3 - \frac{5t} 3$$
|
|
|
|
|
|
|
|
4. Substitute $x_2$ and $x_3$ into $R_1''$:
|
|
|
|
|
|
|
|
$$R_1'' = x_1 + \frac 1 3 - \frac{5t} 3 + 2t = 1 \rightarrow x_1 = \frac 2 3 - \frac t 3$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
## Systems of Equations and Matrices
|
|
|
|
|
|
|
|
Many problems in engineering have a very large number of unknowns and equations to solve
|
|
|
|
simultaneously.
|
|
|
|
We can use matrices to solve these efficiently.
|
|
|
|
|
|
|
|
Take the following simultaneous equations::
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
3x_1 + 4x_2 &= 2 &\text{(1)} \\
|
|
|
|
x_1 + 2x_2 &= 0 &\text{(2)}
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
They can be represented by the following matrices:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
A &= \begin{pmatrix} 3 & 4 \\ 1 & 2 \end{pmatrix} \\
|
|
|
|
\pmb x &= \begin{pmatrix} x_1 \\ x_2 \end{pmatrix} \\
|
|
|
|
\pmb b &= \begin{pmatrix} 2 \\ 0 \end{pmatrix} \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
You can then express the system as:
|
|
|
|
|
|
|
|
$$A\pmb x = \pmb b$$
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### A 3x3 System as a Matrix
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
2x_1 + 3x_2 - x_3 &= 5 \\
|
|
|
|
4x_1 + 4x_2 - 3x_3 &= 3 \\
|
|
|
|
2x_1 - 3x_2 + x_3 &= -1
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
Could be expressed in the form $A\pmb x = \pmb b$ where:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
A &= \begin{pmatrix} 2 & 3 & -1 \\ 4 & 4 & -3 \\ 2 & -3 & -1 \end{pmatrix} \\
|
|
|
|
\pmb x &= \begin{pmatrix} x_1 \\ x_2 \\ x_3 \end{pmatrix} \\
|
|
|
|
\pmb b &= \begin{pmatrix} 5 \\ 3 \\ -1 \end{pmatrix} \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### An $m\times n$ System as a Matrix
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
a_{11}x_1 + a_{12}x_2 + \cdots + a_{1n}x_n &= b_1 \\
|
|
|
|
a_{21}x_1 + a_{22}x_2 + \cdots + a_{2n}x_n &= b_2 \\
|
|
|
|
\cdots \\
|
|
|
|
a_{m1}x_1 + a_{m2}x_2 + \cdots + a_{mn}x_n &= b_m \\
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
Could be expressed in the form $A\pmb x = \pmb b$ where:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
A = \begin{pmatrix} a_{11} & a_{12} & \cdots & a_{1n} \\
|
|
|
|
a_{21} & a_{22} & \cdots & a_{2n} \\
|
|
|
|
\vdots & & & \vdots \\
|
|
|
|
a_{m1} & a_{m2} & \cdots & a_{mn}
|
|
|
|
\end{pmatrix},
|
|
|
|
\pmb x = \begin{pmatrix} x_1 \\ x_2 \\ \vdots \\ x_n \end{pmatrix},
|
|
|
|
\pmb b = \begin{pmatrix} b_1 \\ b_2 \\ \vdots \\ b_m \end{pmatrix}
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
# Matrices
|
|
|
|
|
|
|
|
## Order of a Matrix
|
|
|
|
|
|
|
|
The order of a matrix is its size e.g. $3\times2$ or $m\times n$
|
|
|
|
|
|
|
|
## Column Vectors
|
|
|
|
|
|
|
|
- Column vectors are matrices with only one column:
|
|
|
|
|
|
|
|
$$ \begin{pmatrix} 1 \\ 2 \end{pmatrix} \begin{pmatrix} 4 \\ 45 \\ 12 \end{pmatrix} $$
|
|
|
|
|
|
|
|
- Column vector variables typed up or printed are expressed in $\pmb{bold}$ and when it is
|
|
|
|
handwritten it is \underline{underlined}:
|
|
|
|
|
|
|
|
$$ \pmb x = \begin{pmatrix} -3 \\ 2 \end{pmatrix}$$
|
|
|
|
|
|
|
|
## Matrix Algebra
|
|
|
|
|
|
|
|
### Equality
|
|
|
|
|
|
|
|
Two matrices are the same if:
|
|
|
|
|
|
|
|
- Their order is the same
|
|
|
|
- Their corresponding elements are the same
|
|
|
|
|
|
|
|
### Addition and Subtraction
|
|
|
|
|
|
|
|
Only possible if their order is the same.
|
|
|
|
\begin{align*}
|
|
|
|
A + B&= \begin{pmatrix} a_{11} + b_{11} & a_{12} + b_{12} & \cdots & a_{1n} + b_{1n} \\
|
|
|
|
a_{21} + b_{21} & a_{22} + b_{22} & \cdots & a_{2n} + b_{2n} \\
|
|
|
|
\vdots & & & \vdots \\
|
|
|
|
a_{m1} + b_{m1} & a_{m2} + b_{m2} & \cdots & a_{mn} + b_{mn}
|
|
|
|
\end{pmatrix} \\
|
|
|
|
A - B&= \begin{pmatrix} a_{11} - b_{11} & a_{12} - b_{12} & \cdots & a_{1n} - b_{1n} \\
|
|
|
|
a_{21} - b_{21} & a_{22} - b_{22} & \cdots & a_{2n} - b_{2n} \\
|
|
|
|
\vdots & & & \vdots \\
|
|
|
|
a_{m1} - b_{m1} & a_{m2} - b_{m2} & \cdots & a_{mn} - b_{mn}
|
|
|
|
\end{pmatrix},
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
### Zero Matrix
|
|
|
|
|
|
|
|
This is a matrix whose elements are all zeros.
|
|
|
|
For any matrix $A$,
|
|
|
|
|
|
|
|
$$A + 0 =A$$
|
|
|
|
|
|
|
|
We can only add matrices of the same order, therefore 0 must be of the same order as $A$.
|
|
|
|
|
|
|
|
### Multiplication
|
|
|
|
|
|
|
|
Let
|
|
|
|
|
|
|
|
$$
|
|
|
|
\begin{matrix}
|
|
|
|
A & m\times n \\
|
|
|
|
B & p\times q
|
|
|
|
\end{matrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
To be able to multiply $A$ by $B$, $n = p$.
|
|
|
|
|
|
|
|
If $n \ne p$, then $AB$ does not exist.
|
|
|
|
|
|
|
|
$$
|
|
|
|
\begin{matrix}
|
|
|
|
A & B & = & C \\
|
|
|
|
m\times n & p \times q & & m\times q
|
|
|
|
\end{matrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
When $C = AB$ exists,
|
|
|
|
|
|
|
|
$$C_{ij} = \sum_r\! a_{ir}b_{rj}$$
|
|
|
|
|
|
|
|
That is, $C_{ij}$ is the 'product' of the $i$th row of $A$ and $j$th column of $B$.
|
|
|
|
|
|
|
|
#### Multiplication of a Matrix by a Scalar
|
|
|
|
|
|
|
|
If $\lambda$ is a scalar, we define
|
|
|
|
|
|
|
|
$$
|
|
|
|
\lambda a = \begin{pmatrix} \lambda a_{11} & \lambda a_{12} & \cdots & \lambda a_{1n} \\
|
|
|
|
\lambda a_{21} & \lambda a_{22} & \cdots & \lambda a_{2n} \\
|
|
|
|
\vdots & & & \vdots \\
|
|
|
|
\lambda a_{m1} & \lambda a_{m2} & \cdots & \lambda a_{mn}
|
|
|
|
\end{pmatrix},
|
|
|
|
$$
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$
|
|
|
|
\begin{pmatrix} 1 & -1 \\ 2 & 1 \end{pmatrix}
|
|
|
|
\begin{pmatrix} 0 & 1 \\ 3 & 2 \end{pmatrix} =
|
|
|
|
\begin{pmatrix} -3 & -1 \\ 3 & 4 \end{pmatrix}
|
|
|
|
$$
|
|
|
|
$$
|
|
|
|
\begin{pmatrix} 0 & 1 \\ 3 & 2 \end{pmatrix}
|
|
|
|
\begin{pmatrix} 1 & -1 \\ 2 & 1 \end{pmatrix} =
|
|
|
|
\begin{pmatrix} 2 & 1 \\ 7 & -1 \end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 2
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$
|
|
|
|
A = \begin{pmatrix} 4 & 1 & 6 \\ 3 & 2 & 1 \end{pmatrix},\,
|
|
|
|
B = \begin{pmatrix} 1 & 1 \\ 1 & 2 \\ 1 & 0 \end{pmatrix}
|
|
|
|
$$
|
|
|
|
$$
|
|
|
|
AB = \begin{pmatrix} 11 & 6 \\ 6 & 7 \end{pmatrix},\,
|
|
|
|
BA = \begin{pmatrix} 7 & 3 & 7 \\ 10 & 5 & 8 \\ 4 & 1 & 6 \end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
### Other Properties of Matrix Algebra
|
|
|
|
|
|
|
|
- $(\lambda A)B = \lambda(AB) = A(\lambda B)$
|
|
|
|
- $A(BC) = (AB)C = ABC$
|
|
|
|
- $(A+B)C = AC + BC$
|
|
|
|
- $C(A+B) = CA + CB$
|
|
|
|
- In general, $AB \ne BA$ even if both exist
|
|
|
|
- $AB = 0$ does not always mean $A = 0$ or $B = 0$:
|
|
|
|
|
|
|
|
$$\begin{pmatrix} 0 & 1 \\ 0 & 0 \end{pmatrix} \begin{pmatrix}3 & 0 \\ 0 & 0 \end{pmatrix} =
|
|
|
|
\begin{pmatrix} 0 & 0 \\ 0 & 0 \end{pmatrix} = 0$$
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
It follows that $AB = AC$ does not imply that $B=C$ as
|
|
|
|
|
|
|
|
$$AB = AC \leftrightarrow A(B + C) = 0$$
|
|
|
|
|
|
|
|
and as $A$ and $(B-C)$ are not necessarily 0, $B$ is not necessarily equal to $C$:
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$AB = \begin{pmatrix} 0 & 1 \\ 0 & 0 \end{pmatrix} \begin{pmatrix}0 & 0 \\ 1 & 0 \end{pmatrix} =
|
|
|
|
\begin{pmatrix} 1 & 0 \\ 0 & 0 \end{pmatrix}$$
|
|
|
|
|
|
|
|
and
|
|
|
|
|
|
|
|
$$AC = \begin{pmatrix} 0 & 1 \\ 0 & 0 \end{pmatrix} \begin{pmatrix}1 & 2 \\ 1 & 0 \end{pmatrix} =
|
|
|
|
\begin{pmatrix} 1 & 0 \\ 0 & 0 \end{pmatrix} = AB$$
|
|
|
|
|
|
|
|
but $B \ne C$
|
|
|
|
|
|
|
|
</details>
|
2021-11-02 16:46:30 +00:00
|
|
|
|
|
|
|
## Special Matrices
|
|
|
|
|
|
|
|
### Square Matrix
|
|
|
|
|
|
|
|
Where $m = n$
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
A $3\times3$ matrix.
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$\begin{pmatrix}1 & 2 & 3 \\ 4 & 5 & 6 \\ 7 & 8 & 9\end{pmatrix}$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 2
|
|
|
|
|
|
|
|
A $2\times2$ matrix.
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$\begin{pmatrix}1 & 2 \\ 4 & 5 \end{pmatrix}$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
### Identity Matrix
|
|
|
|
|
|
|
|
The identity matrix is a square matrix whose eleements are all 0, except the leading diagonal which
|
|
|
|
is 1s.
|
|
|
|
The leading diagonal is the top left to bottom right corner.
|
|
|
|
|
|
|
|
It is usually denoted by $I$ or $I_n$.
|
|
|
|
|
|
|
|
The identity matrix has the properties that
|
|
|
|
|
|
|
|
$$AI = IA = A$$
|
|
|
|
|
|
|
|
for any square matrix $A$ of the same order as I, and
|
|
|
|
|
|
|
|
$$Ix = x$$
|
|
|
|
|
|
|
|
for any vector $x$.
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
The $3\times3$ identity matrix.
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$\begin{pmatrix}1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1\end{pmatrix}$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 2
|
|
|
|
|
|
|
|
The $2\times2$ identity matrix.
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$\begin{pmatrix}1 & 0 \\ 0 & 1 \end{pmatrix}$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
### Transposed Matrix
|
|
|
|
|
|
|
|
The transpose of matrix $A$ of order $m\times n$ is matrix $A^T$ which has the order $n\times m$.
|
|
|
|
It is found by reflecting it along the leading diagonal, or interchanging the rows and columns of
|
|
|
|
$A$.
|
|
|
|
|
|
|
|
![by [Lucas Vieira](https://commons.wikimedia.org/wiki/File:Matrix_transpose.gif)](./images/Matrix_transpose.gif)
|
|
|
|
|
|
|
|
Let matrix $D = EF$, then $D^T = (EF)^T = E^TF^T$
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
$$
|
|
|
|
A = \begin{pmatrix}3 & 2 & 1 \\ 4 & 5 & 6 \end{pmatrix},\,
|
|
|
|
A^T = \begin{pmatrix}3 & 4 \\ 2 & 5 \\ 1 & 6\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
#### Example 2
|
|
|
|
|
|
|
|
$$
|
|
|
|
B = \begin{pmatrix}1 \\ 4\end{pmatrix},\,
|
|
|
|
B^T = \begin{pmatrix}1 & 4\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
#### Example 3
|
|
|
|
|
|
|
|
$$
|
|
|
|
C = \begin{pmatrix}1 & 2 & 3 \\ 0 & 5 & 1 \\ 2 & 3 & 7\end{pmatrix},\,
|
|
|
|
C^T = \begin{pmatrix}1 & 0 & 2 \\ 2 & 5 & 4 \\ 3 & 1 & 7\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
### Orthogonal Matrices
|
|
|
|
|
|
|
|
A matrix, $A$, such that
|
|
|
|
|
|
|
|
$$A^{-1} = A^T$$
|
|
|
|
|
|
|
|
is said to be orthogonal.
|
|
|
|
|
|
|
|
Another way to say this is
|
|
|
|
|
|
|
|
$$AA^T = A^TA = I$$
|
|
|
|
|
|
|
|
### Symmetric Matrices
|
|
|
|
|
|
|
|
A square matrix which is symmetric about its leading diagonal:
|
|
|
|
|
|
|
|
$$A = A^T$$
|
|
|
|
|
|
|
|
You can also express this as the matrix $A$, where
|
|
|
|
|
|
|
|
$$a_{ij} = a_{ji}$$
|
|
|
|
|
|
|
|
is satisfied to all elements.
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$\begin{pmatrix}
|
|
|
|
1 & 0 & -1 & 3 \\
|
|
|
|
0 & 3 & 4 & -1 \\
|
|
|
|
-2 & 4 & -1 & 6 \\
|
|
|
|
3 & -7 & 6 & 2
|
|
|
|
\end{pmatrix}$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
### Anti-Symmetric
|
|
|
|
|
|
|
|
A square matrix is anti-symmetric if
|
|
|
|
|
|
|
|
$$A = -A^T$$
|
|
|
|
|
|
|
|
This can also be expressed as
|
|
|
|
|
|
|
|
$$a_{ij} = -a_{ji}$$
|
|
|
|
|
|
|
|
This means that all elements on the leading diagonal must be 0.
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
$$\begin{pmatrix}
|
|
|
|
0 & -1 & 5 \\
|
|
|
|
1 & 0 & 1 \\
|
|
|
|
-5 & -1 & 0
|
|
|
|
\end{pmatrix}$$
|
|
|
|
|
|
|
|
</details>
|
|
|
|
|
|
|
|
## The Determinant
|
|
|
|
|
|
|
|
### Determinant of a 2x2 System
|
|
|
|
|
|
|
|
The determinant of a $2x2$ system is
|
|
|
|
|
|
|
|
$$D = a_{11}a_{22} - a_{12}a_{21}$$
|
|
|
|
|
|
|
|
It is denoted by
|
|
|
|
|
|
|
|
$$
|
|
|
|
\begin{vmatrix}
|
|
|
|
a_{11} & a_{12} \\
|
|
|
|
a_{21} & a_{22}
|
|
|
|
\end{vmatrix}
|
|
|
|
\text{ or }
|
|
|
|
\det
|
|
|
|
\begin{pmatrix}
|
|
|
|
a_{11} & a_{12} \\
|
|
|
|
a_{21} & a_{22}
|
|
|
|
\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
- A system of equations has a unique solution if $D \ne 0$
|
|
|
|
- If $D = 0$, then there are either
|
|
|
|
|
|
|
|
- no solutions (the equations are inconsistent)
|
|
|
|
- intinitely many solutions
|
|
|
|
|
|
|
|
### Determinant of a 3x3 System
|
|
|
|
|
|
|
|
Let
|
|
|
|
|
|
|
|
$$
|
|
|
|
A = \begin{pmatrix}
|
|
|
|
a_{11} & a_{12} & a_{13} \\
|
|
|
|
a_{21} & a_{22} & a_{23} \\
|
|
|
|
a_{31} & a_{32} & a_{33}
|
|
|
|
\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
\det A = &a_{11} \times \det \begin{pmatrix}a_{22} & a_{23} \\ a_{32} & a_{33} \end{pmatrix} \\
|
|
|
|
&-a_{12} \times \det \begin{pmatrix}a_{21} & a_{23} \\ a_{31} & a_{33} \end{pmatrix} \\
|
|
|
|
&+a_{13} \times \det \begin{pmatrix}a_{21} & a_{22} \\ a_{31} & a_{32} \end{pmatrix}
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
The $2x2$ matrices above are created by removing any elements on the same row or column as its corresponding
|
|
|
|
coefficient:
|
|
|
|
|
|
|
|
![](./images/vimscrot-2021-11-02T16:19:40,013146580+00:00.png)
|
|
|
|
|
|
|
|
### Chessboard Determinant
|
|
|
|
|
|
|
|
$\det A$ may be obtained by expanding out any row or column.
|
|
|
|
To figure out which coefficients should be subtracted and which ones added use the chessboard
|
|
|
|
pattern of signs:
|
|
|
|
|
|
|
|
$$\begin{pmatrix} + & - & + \\ - & + & - \\ + & - & + \end{pmatrix}$$
|
|
|
|
|
|
|
|
### Properties of Determinants
|
|
|
|
|
|
|
|
- $$\det A = \det A^T$$
|
|
|
|
- If all elements of one row of a matrix are multiplied by a constant $z$, the determinant of the
|
|
|
|
new matrix is $z$ times the determinant of the original matrix:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
\begin{vmatrix} za & zb \\ c & d \end{vmatrix} &= zad - zbc \\
|
|
|
|
&= z(ad-bc) \\
|
|
|
|
&= z\begin{vmatrix} a & b \\ c & d \end{vmatrix}
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
This is also true if a column of a matrix is mutiplied by a constant.
|
|
|
|
|
|
|
|
**Application** if the fator $z$ appears in each elements of a row or column of a determinant it
|
|
|
|
can be factored out
|
|
|
|
|
|
|
|
$$\begin{vmatrix}2 & 12 \\ 1 & 3 \end{vmatrix} = 2\begin{vmatrix}1 & 6 \\ 1 & 3 \end{vmatrix} = 2 \times 3
|
|
|
|
\begin{vmatrix} 1 & 2 \\ 1 & 1 \end{vmatrix}$$
|
|
|
|
|
|
|
|
**Application** if all elements in one row or column of a matrix are zero, the value of the
|
|
|
|
determinant is 0.
|
|
|
|
|
|
|
|
$$\begin{vmatrix} 0 & 0 \\ c & d \end{vmatrix} = 0\times d - 0\times c = 0$$
|
|
|
|
|
|
|
|
|
|
|
|
**Application** if $A$ is an $n\times n$ matrix,
|
|
|
|
|
|
|
|
$$\det(zA) = z^n\det A$$
|
|
|
|
|
|
|
|
- Swapping any two rows or columns of a matrix changes the sign of the determinant
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
\begin{vmatrix} c & d \\ a & b \end{vmatrix} &= cb - ad \\
|
|
|
|
&= -(ad - bc) \\
|
|
|
|
&= -\begin{vmatrix} a & b \\ c & d \end{vmatrix}
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
**Application** If any two rows or two columns are identical, the determinant is zero.
|
|
|
|
|
|
|
|
**Application** If any row is a mutiple of another, or a column a multiple of another column, the
|
|
|
|
determinant is zero.
|
|
|
|
|
|
|
|
- The value of a determinant is unchanged by adding to any row a constant multiple of another row,
|
|
|
|
or adding to any column a constant multiple of another column
|
|
|
|
|
|
|
|
- If $A$ and $B$ are square matrices of the same order then
|
|
|
|
|
|
|
|
$$\det(AB) = \det A \times \det B $$
|
|
|
|
|
|
|
|
## Inverse of a Matrix
|
|
|
|
|
|
|
|
If $A$ is a square matrix, then its inverse matrix is $A^{-1}$ and is defined by the property that:
|
|
|
|
|
|
|
|
$$A^{-1}A = AA^{-1} = I$$
|
|
|
|
|
|
|
|
- Not every matrix has an inverse
|
|
|
|
- If the inverse exists, then it is very useful for solving systems of equations:
|
|
|
|
|
|
|
|
\begin{align*}
|
|
|
|
A\pmb{x} = \pmb b \rightarrow A^{-1}A\pmb x &= A^{-1}\pmb b \\
|
|
|
|
I\pmb x &= A^{-1}\pmb b \\
|
|
|
|
\pmb x &= A^{-1}\pmb b
|
|
|
|
\end{align*}
|
|
|
|
|
|
|
|
Therefore there must be a unique solution to $A\pmb x = \pmb b$: $\pmb x = A^{-1}\pmb b$.
|
|
|
|
|
|
|
|
- If $D = EF$ then
|
|
|
|
|
|
|
|
$$D^-1 = (EF)^{-1} = F^{-1}E^{-1}$$
|
|
|
|
|
|
|
|
### Inverse of a 2x2 Matrix
|
|
|
|
|
|
|
|
If $A$ is the $2x2$ matrix
|
|
|
|
|
|
|
|
$$
|
|
|
|
A = \begin{pmatrix}
|
|
|
|
a_{11} & a_{12} \\
|
|
|
|
a_{21} & a_{22}
|
|
|
|
\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
and its determinant, $D$, satisfies $D \ne 0$, $A$ has the inverse $A^{-1}$ given by
|
|
|
|
|
|
|
|
$$
|
|
|
|
A^{-1} = \frac 1 D \begin{pmatrix}
|
|
|
|
a_{22} & -a_{12} \\
|
|
|
|
-a_{21} & a_{11}
|
|
|
|
\end{pmatrix}
|
|
|
|
$$
|
|
|
|
|
|
|
|
If $D = 0$, then matrix $A$ has no inverse.
|
|
|
|
|
|
|
|
<details>
|
|
|
|
<summary>
|
|
|
|
|
|
|
|
#### Example 1
|
|
|
|
|
|
|
|
Find the inverse of matrix $A = \begin{pmatrix} -1 & 5 \\ 2 & 3 \end{pmatrix}$.
|
|
|
|
|
|
|
|
</summary>
|
|
|
|
|
|
|
|
1. Calculate the determinant
|
|
|
|
|
|
|
|
$$\det A = -1 \times 3 - 5 \times 2 = -13$$
|
|
|
|
|
|
|
|
Since $\det A \ne 0$, the inverse exists.
|
|
|
|
|
|
|
|
2. Calculate $A^{-1}$
|
|
|
|
|
|
|
|
$$ A^{-1} = \frac 1 {-13} \begin{pmatrix} 3 & -5 \\ -2 & -1\end{pmatrix}$$
|